Decyzja administracyjna wydawana w postępowaniu o ponowne wykorzystywanie informacji sektora publicznego w wyniku sprzeciwu. Zagadnienia wybrane - Piskorz-Ryń, Agnieszka; Wyporska-Frankiewicz, Joanna (Kwartalnik Prawa Publicznego, 2016)
The article presents problems related to the method of regulation by the Polish legislator of the mode of transfer of public sector information upon request, based on example of the administrative decision referred to in Article. 23 paragraph. 3 of the Act on re-use of public sector information. This mode merges elements of administrative law and civil law in a single procedure, which is an example of a hybrid proceedings. The article takes a negative view of the adopted solutions. The right to re-use is primarily an economic law and the purpose of the Act was to ensure equal and non-discriminatory rules for re-use and undistorted competition in the market. Hybrid developed by the legislation has a negative impact on the situation of the party raising an objection, clearly preferring the user which accepts the content of the offer. This does not concern extending the proceedings, as a natural consequence of controlling legality of the legal action, but changing the nature of that relationship.